{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

QuizFormulas10

# QuizFormulas10 - z = p-p p p(1-p/n p 1 p 2 z s p 1(1 p 1 n...

This preview shows page 1. Sign up to view the full content.

STAT 212: Quiz 10 Formulas ¯ x = 1 n n X i =1 x i s 2 = 1 n - 1 n X i =1 ( x i - ¯ x ) 2 = 1 n - 1 ( n X i =1 x 2 i - ( n i =1 x i ) 2 n ) s = s 2 r = 1 n - 1 n X i =1 x i - ¯ x s x y i - ¯ y s y ˆ y = b 0 + b 1 x ; b 1 = r s y s x , b 0 = ¯ y - b 1 ¯ x μ X = X x i p i σ 2 X = X ( x i - μ X ) 2 p i σ 2 a + bX = b 2 σ 2 X σ 2 X + Y = σ 2 X + σ 2 Y + 2 ρσ X σ Y σ 2 X - Y = σ 2 X + σ 2 Y - 2 ρσ X σ Y μ ¯ x = μ ; σ ¯ x = σ n P ( X = k ) = n ! k !( n - k )! p k (1 - p ) n - k ; μ = np, σ = p np (1 - p ) P ( X = k ) = e - μ μ k k ! ¯ x ± z * σ n n = z * σ m 2 z = ¯ x - μ ( σ/ n ) t = ¯ x - μ ( s/ n ) ¯ x ± t * s n z = x 1 - ¯ x 2 ) - ( μ 1 - μ 2 ) q σ 2 1 n 1 + σ 2 2 n 2 t = x 1 - ¯ x 2 ) - ( μ 1 - μ 2 ) q s 2 1 n 1 + s 2 2 n 2 x 1 - ¯ x 2 ) ± t * s s 2 1 n 1 + s 2 2 n 2 ˆ p ± z * r ˆ p (1 - ˆ p ) n
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ) z = p-p p p (1-p ) /n ( p 1- p 2 ) z * s p 1 (1- p 1 ) n 1 + p 2 (1- p 2 ) n 2 z = ( p 1- p 2 ) r p (1- p ) 1 n 1 + 1 n 2 , p = X 1 + X 2 n 1 + n 2...
View Full Document

{[ snackBarMessage ]}